Increased cancer risk in patients with cutaneous lupus erythematosus and systemic lupus erythematosus compared with the general population: A Danish nationwide cohort study. (April 2021) - Westermann, Rasmus; Zobbe, Kristian; Cordtz, René; Haugaard, Jeanette H; Dreyer, Lene
Objectives: To investigate if patients with cutaneous lupus erythematosus (CLE) or systemic lupus erythematosus (SLE) have an increased risk of cancer compared with the general population, and furthermore to identify specific cancer types associated with increased risk. Methods: This is an observational cohort study of 5310 patients with CLE or SLE identified in the Danish National Patient Register from 1 January 1995 to 31 December 2014. The cohort was followed up for cancer by linkage to the Danish Cancer Registry. Based on the age, sex, and calendar specific cancer rates of the general population of Denmark, standardised incidence ratios (SIRs) were calculated. Results: The patients with CLE or SLE were followed for 40.724 person-years, each group's average duration of follow-up being 6.9 and 8.1 years. The SIR for overall cancer (except non-melanoma skin cancer (NMSC)) was increased in patients with CLE 1.35 (95%CI 1.15 to 1.58) and patients with SLE 1.45 (95%CI 1.30 to 1.62). Both groups had high risks of hematological – including a 3–4-fold increased risk of non-Hodgkin lymphoma –, pancreatic, and lung cancers. Several cancers associated with oncogenic viruses as liver and tongue/mouth/pharynx were increased in the SLE group, while the risk of ovarian cancer was increased 2–4-fold only in the CLE group. Conclusion: The overall risk of cancer was significantly increased in both patients with CLE and SLE. SIRs for hematological, pancreatic and lung cancers were elevated in both groups. Extra awareness of cancer in patients with SLE and patients with CLE should be considered.